Appropriate Technology-Based Dental and Oral Health Care Model for Orphanage Children - Purwati, Dwi Eni; Suyatmi, Dwi; Eldarita; prasetyowati, silvia; Dewi, Filanti Kusuma; Fitriyanti, Luci (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Dental And Oral Health Care Service Model Based On Appropriate Technology in The Orphanage Community. Residents of orphanages are school-age children in groups who are prone to tooth decay and whose rights and needs are no different from other children their age. Appropriate technology assistance (TTG) is needed to overcome dental and oral health problems in orphanage children. The general objective of this research is to produce a feasible model of appropriate technology-based dental and oral health care (TTG) services and their effective application to improve dental and oral health in orphanage children. The method in this study uses the R&D (Research and Development) method with Pre- Experimental Pretest and Posttest Design research design. Respondents numbered 20 dental health cadres to assess behavior (knowledge, attitudes, actions) and 150 orphanage children (OHI-S; DMF-T). Expert validation test of dental and oral health care service modules based on appropriate technology (TTG) amounted to 67.60% real. Knowledge assessments and actions improved significantly after treatment (p=<0.001, p=0.004, respectively). Attitude assessment did not increase compared to the previous (p = 0.005). The behavior of dental health cadres did not affect OHIS and DMFT (p=0.62, p=0.20, respectively). It can be concluded that the appropriate technology-based dental and oral health care (TTG) service model provides a significant increase in the knowledge and actions of dental health cadres but does not improve attitudes, OHIS, and DMFT.